PARK2-dependent mitophagy induced by acidic postconditioning protects against focal cerebral ischemia and extends the reperfusion window. Issue 3 (4th March 2017) - Shen, Zhe; Zheng, Yanrong; Wu, Jiaying; Chen, Ying; Wu, Xiaoli; Zhou, Yiting; Yuan, Yang; Lu, Shousheng; Jiang, Lei; Qin, Zhenghong; Chen, Zhong; Hu, Weiwei; et al.
ABSTRACT: Prompt reperfusion after cerebral ischemia is critical for neuronal survival. Any strategies that extend the limited reperfusion window will be of great importance. Acidic postconditioning (APC) is a mild acidosis treatment that involves inhaling CO2 during reperfusion following ischemia. APC attenuates ischemic brain injury although the underlying mechanisms have not been elucidated. Here we report that APC reinforces ischemia-reperfusion-induced mitophagy in middle cortical artery occlusion (MCAO)-treated mice, and in oxygen-glucose deprivation (OGD)-treated brain slices and neurons. Inhibition of mitophagy compromises neuroprotection conferred by APC. Furthermore, mitophagy and neuroprotection are abolished in Park2 knockout mice, indicating that APC-induced mitophagy is facilitated by the recruitment of PARK2 to mitochondria. Importantly, in MCAO mice, APC treatment extended the effective reperfusion window from 2 to 4 h, and this window was further extended to 6 h by exogenously expressing PARK2. Taken together, we found that PARK2-dependent APC-induced mitophagy renders the brain resistant to ischemic injury. APC treatment could be a favorable strategy to extend the thrombolytic time window for stroke therapy.